Exploring college-student insights on learning aids and practicum equipment - The, Hery Yanto; Sujata, Dian Tika (Jurnal Inovasi Teknologi Pendidikan, 2025)
Reflecting on the use of learning media will help students decide on a quality and user-friendly design. Thus, this study examines the experiences of second-year students in the Buddhist Religious Education program at Institut Nalanda who participated in the online distance "Learning Media" course during the 2023-2024 academic year. The researcher aims to understand the students' perspectives on the impact of instructional and practical equipment on their learning. This study used a case study technique, specifically the classroom research strategy, to collect data from 37 student forum posts on Google Classroom. Following a solitary session of asynchronous lectures, comprising a teaching module and three audio recordings, the students produced these postings. The researcher employed qualitative descriptive analysis, utilizing QDA Miner, to discern the principal themes and conclusions derived from the data. The data indicates that students had a variety of experiences using both instructional and practical equipment. Students experience the use of teaching aids to facilitate science experiments, classroom demonstrations, and accounting learning and support arts and sports classes. This study found that students have positive impressions of these media based on their learning experiences. Reflecting on their own learning experiences can inspire students to develop their learning media as a class project. The findings of this study can assist educators in designing learning environments that more effectively prepare students for academic and professional challenges. Research on other cohorts can be conducted as longitudinal studies. Comparing students' experience of on-site and online classes can also be done as a future study.